Pomset bisimulation and unfolding for reset Petri nets - CHATAIN, THOMAS; Comlan, Maurice; DELFIEU, DAVID; JEZEQUEL, LOIG; Roux, Olivier (My University, 2020)
Reset Petri nets are a particular class of Petri nets where transition firings can remove all tokens from a place without checking if this place actually holds tokens or not. In this paper we look at partial order semantics of reset Petri nets. In particular, we propose a pomset bisimulation for comparing their concurrent behaviours. Building on this pomset bisimulation we then propose a generalization of the standard finite complete prefixes of unfolding for this class of Petri nets.
Keywords: Reset Petri nets; Pomset behaviour; Unfolding